2021
DOI: 10.1155/2021/3448979
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Effect of Cluster Nursing in Postoperative Hypertensive Cerebral Hemorrhage

Abstract: Hypertensive intracerebral hemorrhage is a common condition in clinic. Due to the improvement of minimally invasive technology, its therapeutic effect is good, but there are still postoperative complications. The corresponding routine nursing intervention is not effective in the rehabilitation of postoperative patients with hypertensive intracerebral hemorrhage. In this paper, cluster nursing was applied to the treatment of postoperative patients with hypertensive intracerebral hemorrhage. For this purpose, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Most individuals with chronic illnesses have psychological issues that impede recovery of the disease [ 11 ]. The cluster nursing mode prioritizes psychological nursing, assesses patients’ psychological requirements, and then implements targeted psychological nursing to alleviate patients’ negative psychological feelings and maintain their psychological well-being [ 34 ]. In our study, we also found that the anxiety scores and depression scores of the intervention group were lower than those of the control group, which agrees with the results of other studies [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals with chronic illnesses have psychological issues that impede recovery of the disease [ 11 ]. The cluster nursing mode prioritizes psychological nursing, assesses patients’ psychological requirements, and then implements targeted psychological nursing to alleviate patients’ negative psychological feelings and maintain their psychological well-being [ 34 ]. In our study, we also found that the anxiety scores and depression scores of the intervention group were lower than those of the control group, which agrees with the results of other studies [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%